2021
DOI: 10.1186/s40337-021-00395-8
|View full text |Cite
|
Sign up to set email alerts
|

Believing emotions are uncontrollable is linked to eating disorder psychopathology via suppression and reappraisal

Abstract: Objective Research suggests that beliefs about emotional controllability influence the use of emotion regulation strategies, which in turn impact psychological health and illness. However, no research has yet investigated whether emotional controllability is linked to eating psychopathology. The current study investigates whether these concepts are related, as individuals with eating disorders have problems with emotion regulation. Method We collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…In past work, it has similarly been found that the controllability domain is the strongest predictor of psychopathology and emotion regulation (see Becerra et al, 2020). Recent studies have also supported that believing emotions are uncontrollable was linked to psychopathology symptoms via usage of maladaptive emotion regulation strategies (De Castella et al, 2013;Vuillier et al, 2021). Therefore, our results are in line with previous reports (Becerra et al, 2020), in so far supporting a more significant role of the controllability beliefs domain in predicting symptoms of psychopathology.…”
Section: The Predictive Role Of Emotion Beliefs In Mental Health Symp...supporting
confidence: 92%
“…In past work, it has similarly been found that the controllability domain is the strongest predictor of psychopathology and emotion regulation (see Becerra et al, 2020). Recent studies have also supported that believing emotions are uncontrollable was linked to psychopathology symptoms via usage of maladaptive emotion regulation strategies (De Castella et al, 2013;Vuillier et al, 2021). Therefore, our results are in line with previous reports (Becerra et al, 2020), in so far supporting a more significant role of the controllability beliefs domain in predicting symptoms of psychopathology.…”
Section: The Predictive Role Of Emotion Beliefs In Mental Health Symp...supporting
confidence: 92%
“…Participants completed a number of measures which were presented through the online platform Qualtrics. Participants also answered other questionnaires not reported in the current paper, and some of the data was used in two published articles [ 19 , 62 ]. The measures relevant to the present analysis as predictors, dependent variables and covariates were as follows:…”
Section: Methodsmentioning
confidence: 99%
“…In addition, future empirical work could clarify potential mediators and moderators in the relationships between emotion perspectives and clinical outcomes. Initial work in this domain has clarified that differences in emotion regulation, such as the use of cognitive reappraisal or expressive suppression, mediated the relationship between emotion perspectives and mental health, including depressive, anxiety, and eating disorder symptoms (Deplancke et al, 2022 ; Vuillier et al, 2021 ). Additionally, work by Schroder and others describe how anxiety mindsets related to clinical symptoms, such as substance use, depression, and non-suicidal self-injury, and buffered the effect of stressful life events on certain symptoms (Schroder et al, 2017 ).…”
Section: Overview Of Papers and Research Themes Included In The Speci...mentioning
confidence: 99%